The type specimens of Bebryce (Cnidaria, Octocorallia, Plexauridae) re-examined, with emphasis on the sclerites - Bayer, F.m.; Ofwegen, L.p. Van (Zootaxa, 2016)
Nineteen species of Bebryce are re-described and scanning electron microscopy (SEM) images of sclerites presented. For B. sulfurea Grasshoff, 2000, this is the first time SEM images of sclerites are presented. Two new species are described, Bebryce asteria n. sp. and B. cofferi n. sp., and B. stellata Hentschel, 1903 is synonymized with B. studeri Whitelegge, 1897. Bebryce acanthoides Thomson & Russell, 1910 is referred to Discogorgia Kükenthal, 1919. The status of the original type material is discussed.